IOS Development with Xamarin Cookbook - Tavlikos, Dimitris (Packt Publishing, 2014)
In Detail This book will provide you with the necessary knowledge and skills to be part of the mobile development era, using C♯. Covering a wide range of recipes such as creating a simple application and using device features effectively, it will be your companion to the complete application development cycle. Starting from installing the necessary tools, you will be guided step-by-step on everything you need to develop an application ready to be deployed. You will learn the best practices for interacting with the device hardware, such as the GPS, compass, and the accelerometer. Furthermore, you will be able to manage multimedia resources such as photos and videos captured with the device camera, and much more!Approach The book is written in a recipe format with practical examples, allowing you to go directly to your topic of interest or follow topics throughout a chapter to gain an in-depth knowledge. There are also plenty of hints and best practices along the way. Who this book is for If you are a C♯/.NET developer with no previous experience in iOS development or an Objective-C developer who wants to create complete iOS applications and deploy them to the App Store, then this book is ideal for you. No experience with Xamarin is needed.